Gamma knife radiosurgery for uveal melanomas and metastases: a systematic review and meta-analysis. Issue 11 (November 2020) - Parker, Tariq; Rigney, Grant; Kallos, Justiss; Stefko, S Tonya; Kano, Hideyuki; Niranjan, Ajay; Green, Alexander L; Aziz, Tipu; Rath, Pamela; Lunsford, L Dade
Summary: Background: Gamma knife radiosurgery is regarded as the gold-standard stereotactic radiosurgery modality for the treatment of intracranial tumours, and its use has been expanded for the treatment of intraocular malignancies. The aim of this study was to systematically evaluate the efficacy, outcomes, and complications of gamma knife radiosurgery for uveal melanomas and metastases. Methods: We did a systematic review and meta-analysis to aggregate the clinical outcomes of patients with uveal melanomas or intraocular metastases treated primarily with gamma knife radiosurgery. We searched MEDLINE and Embase for studies published between Sept 1, 1960, and Feb 1, 2020, reporting the use of gamma knife radiosurgery as primary treatment for uveal melanoma or uveal metastases. The search was restricted to clinical studies and relevant grey literature published in English. Studies reporting treatment of benign tumours, extraocular tumours, or other forms of stereotactic radiosurgery were excluded to reduce heterogeneity. No restrictions were placed on participant criteria. Local tumour control and tumour regression were extracted as the primary outcomes and analysed via a random-effects meta-analysis of proportions using the DerSimonian and Laird method with a Freeman-Tukey double arcsine transformation. This study is registered with PROSPERO, CRD42019148165. Findings: Our search returned 454 studies, of which 109 were assessed for full-text eligibility. 52 studies, reporting on 1010 patients with uveal melanoma and 34 intraocular metastases, were eligible for systematic review. 28 studies were included in the meta-analysis. 840 of 898 patients (0·96, 95% CI 0·94–0·97; I 2 =16%) from 19 studies had local control, and 378 of 478 patients (0·81, 0·70–0·90; I 2 =83%) from 16 studies experienced tumour regression. Interpretation: Gamma knife radiosurgery is an efficacious primary method of treating uveal melanomas and intraocular metastases, with reliable tumour control rates. Randomised controlled trials should further evaluate the safety and efficacy of gamma knife radiosurgery in this setting. Funding: The Rhodes Trust and the Howard Brain Sciences Foundation.